(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the life and scholarly-spiritual legacy of our compatriot, Imam Abu Mansur al-Maturidi, one of the most prominent representatives of the science of Kalam. The article highlights pedagogically the tolerance-based ideas of Maturidi’s teachings, which were founded by the scholar himself. Furthermore, the significance of Imam Maturidi’s works in countering various heterodox ideas is analyzed.